Authentication and Encryption Drone Communication by Using HIGHT Lightweight Algorithm - et. al., Hani M. Ismael, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Extensive use of unmanned aerial vehicles (commonly referred to as a “drone”) has posed security and safety challenges. To mitigate security threats caused by flights of unauthorized drones, we proposed an authentication and security system based on the Chaotic maps and stream cipher lightweight HIGHT algorithm. The proposed system is specifically designed aims to minimize the computational and lower consumption of drone resources and deal with one ground control station (GCS) and one Drone with the number of fly sessions. The proposed system initially generates a flight session key for a drone having a flight plan based on the proposed key generation method using 1d Chebyshev chaotic map and registers the flight session key and its flight plan into a centralized database that can be accessed by. Then drone using HIGHT lightweight to cipher payload data to increase security MAVLink communication protocol and send it to GCS, and finally a GCS checks authentication of the current flight session based on the flight session key and its flight plan as the message authentication code key to authenticate the drone by any flight session while the drone is flying. The experiment results using the NIST test prove the proposed key generation method is able to produce unique and random fly session key, also the results of the error sensitive metrics proved the security of the proposed system using HIGHT block cipher lightweight that is an automatic cryptographic protocol verifier.